Qualitative Inquiry and the Conservative Challenge : Confronting Methodological Fundamentalism. - Denzin, Norman K. (Left Coast Press, 2006)
This volume is a call to qualitative researchers to respond to the political and methodological conservativism of the new millennium by emphasizing ethical practice and social justice.